ENT 530 : Case Study: The Honest Treat / Liyana Maisarah Nazri ... [et al.] - Nazri, Liyana Maisarah; Abdul Halim, Nurul Syafiqah; Azahari, Amirah Nur Afrina; Hazlan, Nik Amira Batrisyia; Abd Aziz, Siti Zulaikha (2021)
During this Covid 19 pandemic, a lot of people were affected in income and salary. Therefore, they are involved in business activities such as brick and mortar which include online and offline business. It helps people to generate income during this pandemic due to some of them having been fired by their company or reduced in their monthly salary. In this case study, we had done research about the Small Medium Enterprise (SME)’s company which we know that most of them were affected in their sales and services due to the pandemic. They are trying to survive in order to continue their life and pay for their business expenses such as rent, utilities and so on. On 5 April 2021, we had an interview with the Manager of The Honest Treat , Puan Fatin Liyana binti Khalid. The interview session was held by using Google meet platform. We had collected a lot of information during the interview session such as the company's background, company’s organization structure, the purpose of the business and types of products, the mission of the company, their marketing strategy and the problem that occurred due to Covid 19 pandemic. The interview session went smoothly for more than one hour. Puan Fatin Liyana is a very professional person as she explained clearly about her company and was willing to answer all of our questions. From the interview session, we had found that The Honest Treat company had several problems. The major issue in her business is wasted food stocks. To overcome the problems, the company should project the future orders and demands from customers and find the good suppliers to buy the food stocks in bulk and get a discount pricing. Besides, the company should understand their market demand so that they know how much their products can be sold in a month and buy the exact amount of food stocks for the next month. Therefore, the company can control their costs and not over-buying the food stocks. Moreover, the company also faced staffing problem issues. This is because most of the workers only work for only 2-3 month. However, the company needs a lot of human energy due to a lot of customers during the pandemic. Besides, the company had wasted a lot of time to carry out a baking training class for the new workers but suddenly the workers only worked for 2-3 month. We suggest that the company make an agreement before hiring a worker. For example, the workers need to work at least for a year in the company before they want to find another job.